2018
DOI: 10.1080/09712119.2018.1512862
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a protease to low crude protein density diets of broiler chickens

Abstract: A total of 864 1-day-old Ross 308 broiler chickens with an average body weight of 40 ± 1.1 g were used to determine the effect of adding protease to broiler chickens diets with different crude protein (CP) density on growth performance, carcase characteristics, excreta microbiota, blood constituents, and nutrient digestibility. The chicks were allotted in pens with 18 birds/pen and 12 pen/treatment. Treatments were T1: basal diet, T2: T1 − 1.0% CP, T3: T2 + 0.05% protease, T4: T2 + 0.1% protease. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
5
14
0
1
Order By: Relevance
“… Farhat and Chavez (1999) observed changes in breast muscle thickness using ultrasound showing values of 8.42, 7.26, and 6.93 mm for high (23%), medium (19%), and low protein (17%) programs, respectively. Mohammadigheisar et al. (2018) found that feeding broiler chickens with LP diets had no effect on breast meat yield.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… Farhat and Chavez (1999) observed changes in breast muscle thickness using ultrasound showing values of 8.42, 7.26, and 6.93 mm for high (23%), medium (19%), and low protein (17%) programs, respectively. Mohammadigheisar et al. (2018) found that feeding broiler chickens with LP diets had no effect on breast meat yield.…”
Section: Discussionmentioning
confidence: 97%
“…(2002) found that supplemented protease had been applied to LP diets without deleterious effects on the performance of broiler chickens. Supplemental exogenous proteases have been found to improve protein digestibility, energy efficiency, and performance indices in broilers ( Fru-Nji et al., 2011 ), even in a LP diet ( Cowieson et al., 2017 , Lei et al., 2017 , Morales et al., 2017 , Law et al., 2018 , Mohammadigheisar and Kim, 2018 ), which indicated that reducing dietary CP levels with exogenous supplementation can be used for production. However, to our knowledge, no data are available concerning the supplementation of protease to reduced CP levels of diets in ducks.…”
Section: Introductionmentioning
confidence: 99%
“…반대로 xylanase를 사 료에 배합하였을 때 Lactobacillus 등 장내 균총 변화에 영향 을 미치지 않았다 (Lu et al, 2009). 또한, 본 연구와 유사한 이 전 연구에서 조단백질 수준을 낮추고, 프로테아제 효소제를 급여하는 실험에서도 마찬가지로 총균수, 유산균수, 대장균수 에서 유의적인 차이는 발생하지 않았다 (Mohammadigheisar and Kim, 2018 2 Control diet, balanced diet; T1, diet with reduction of 100 kcal ME/kg and 1% of CP and addition of 4,000 μ/g xylanase, 400 μ/g α-amylase, and 8,000 μ/g protease; T2, diet with reduction of 100 kcal ME/kg and 1% of CP and addition of 800 μ/g βmannanase; T3, diet with reduction of 100 kcal ME/kg and 1% of CP and addition of 2,200 μ/g xylanase and 200 μ/g βglucanase; T4, diet with reduction of 100 kcal ME/kg and 1% of CP and addition of 1,000 μ/g xylanase. 3 SEM, standard error of the mean.…”
Section: 동물 사료 및 실험설계unclassified
“…In order to reduce the environmental pollution and feed cost of poultry husbandry, a method of reducing crude protein (CP) content in diet was put forward. However, it has been reported that reducing crude protein in diet has negative effects on the performance of birds (Mohammadigheisar and Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%